Адаптація першокурсників – майбутніх соціальних працівників до умов навчання в закладі вищої освіти - Равлюк, Тетяна Анатоліївна (Київ «Перспективи та інновації науки», 2023)
In the professional development and self-realization of future social workers, a successful adaptation process to the new conditions of study in a higher education institution is of great importance. This is due to a change in the mode of the day, increased physical activity, reduced time for sleep and rest, the establishing new contacts with classmates, teachers, etc. The article highlights the scientific approaches to the definition of the term "adaptation" (biological, physiological, socio-psychological, psychological, and activity). It is stated that adaptation in a higher education institution is interpreted as a complex multifaceted psychological and pedagogical process of adaptation of freshmen to new teaching methods, norms of the student team; mastering the norms and functions of future professional activity. This, accordingly, determines the formation of ideals, values, personal qualities, and professional success in the future. The role of the academic discipline "Introduction to the specialty" in the gradual adaptation of freshmen majoring in "Social Work" to the new conditions of the educational process in higher education institutions is determined. The results of a survey of first-year students majoring in "Social Work" of Chernivtsi National University named after Yuri Fedkovich are analyzed. The questionnaire in the Google form consisted of two parts and was conducted in two stages (in September and November 2023). Among the difficulties mentioned by the respondents were internal (low memory development, laziness, etc.) and external factors (changing the daily routine, establishing interaction with others, etc.). Taking into account the students' answers, we believe that the use of interactive forms of interaction (in classes, in extracurricular activities) will contribute to increase adaptive mobility, the formation of skills to perceive new conditions without stress, the ability to quickly change their behavior; at the levels of "curator-student", "student-student", "teacher-student", "social work specialist-student", etc.
Keywords: adaptation, adaptation in a higher education institution, "Introduction to the specialty", difficulties of adaptation of freshmen